Access to enantiopure α-alkyl-β-hydroxy esters through dynamic kinetic resolutions employing purified/overexpressed alcohol dehydrogenases - Cuetos, Aníbal (2012)
α-Alkyl-β-hydroxy esters were obtained via dynamic kinetic resolution (DKR) employing purified or crude E. coli overexpressed alcohol dehydrogenases (ADHs). ADH-A from R. ruber, CPADH from C. parapsilosis and TesADH from T. ethanolicus afforded syn-(2R,3S) derivatives with very high selectivities for sterically not impeded ketones ('small-bulky' substrates), while ADHs from S. yanoikuyae (SyADH) and Ralstonia sp. (RasADH) could also accept bulkier keto esters ('bulky-bulky' substrates). SyADH also provided preferentially syn-(2R,3S) isomers and RasADH showed in some cases good selectivity towards the formation of anti-(2S,3S) derivatives. With anti-Prelog ADHs such as LBADH from L. brevis or LKADH from L. kefir, syn-(2S,3R) alcohols were obtained with high conversions and diastereomeric excess in some cases, especially with LBADH. Furthermore, due to the thermodynamically favoured reduction of these substrates, it was possible to employ just a minimal excess of 2-propanol to obtain the final products with quantitative conversions. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.